Relations industrielles et nouveaux systèmes productifs : recherche, politiques et pratiques - Murray, Gregor; Lapointe, Paul-André; Bélanger, Jacques; Giles, Anthony (Relations industrielles / Industrial Relations, 1999)
Présente le colloque international coparrainé par le Centre de relations industrielles de l'Université Laval et le Réseau canadien de recherche sur les milieux de travail qui s'est tenu en septembre 1997.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; R&D; Research; Research & development; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Industrial relations in the new workplace: research, policy and practice - Giles, Anthony; Lapointe, Paul-André; Murray, Gregor; Bélanger, Jacques (Relations industrielles / Industrial Relations, 1999)
Introduces the international colloquium co-sponsored by Laval University's Industrial Relations Centre and the Canadian Workplace Research Network held in September 1997.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; R&D; Research; Research & development; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z